Unsettled narratives : the Pacific writings of Stevenson, Ellis, Melville and London - Farrier, David, 1979- (Literary criticism and cultural theory., 2007)
Acknowledgments ix. Introduction: The Written Pacific 1 (14). ``Talk languished on the beach'': The Possibility of Reciprocity in Robert Louis Stevenson's In the South Seas. 15 (58). ``These words are so changed in a native's mouth'': Contested Frames in William Ellis's Polynesian Researches. 73 (44). ``Typee or Happar?'': The Unsettling Narrative of Typee. 117 (56). ``This is the Book I write'': Jack London's Strictly Limited Body. 173 (54). Conclusion: Ambivalence and Authorship 227 (6). Notes 233 (32). Works Cited 265 (8). Index.